SENP3 regulates the global protein turnover and the Sp1 level via antagonizing SUMO2/3-targeted ubiquitination and degradation. Issue 1 (28th October 2015) - Wang, Ming; Sang, Jing; Ren, Yanhua; Liu, Kejia; Liu, Xinyi; Zhang, Jian; Wang, Haolu; Wang, Jian; Orian, Amir; Yang, Jie; Yi, Jing
Abstract: SUMOylation is recently found to function as a targeting signal for the degradation of substrates through the ubiquitin-proteasome system. RNF4 is the most studied human SUMO-targeted ubiquitin E3 ligase. However, the relationship between SUMO proteases, SENPs, and RNF4 remains obscure. There are limited examples of the SENP regulation of SUMO2/3-targeted proteolysis mediated by RNF4. The present study investigated the role of SENP3 in the global protein turnover related to SUMO2/3-targeted ubiquitination and focused in particular on the SENP3 regulation of the stability of Sp1. Our data demonstrated that SENP3 impaired the global ubiquitination profile and promoted the accumulation of many proteins. Sp1, a cancer-associated transcription factor, was among these proteins. SENP3 increased the level of Sp1 protein via antagonizing the SUMO2/3-targeted ubiquitination and the consequent proteasome-dependent degradation that was mediated by RNF4. De-conjugation of SUMO2/3 by SENP3 attenuated the interaction of Sp1 with RNF4. In gastric cancer cell lines and specimens derived from patients and nude mice, the level of Sp1 was generally increased in parallel to the level of SENP3. These results provided a new explanation for the enrichment of the Sp1 protein in various cancers, and revealed a regulation of SUMO2/3 conjugated proteins whose levels may be tightly controlled by SENP3 and RNF4.